E-Hailing Transportation and the Issue of Competition in Indonesia - Rizaldy Anggriawan (Indonesian Comparative Law Review, 2019)
E-hailing transportation can be an alternative solution for both fulfilling the increasing demand for public transportation and reducing the number of vehicles on the road. As a populated country, Indonesia has benefited much from the emergence of e-hailing transportation. Unfortunately, despite positive impacts that have been enjoyed, numerous issues have arisen along with the growth of e-hailing transportation in the country. There are several indications that e-hailing companies have been involving in an unfair competition, including predatory pricing. This is done by offering very low fare of transportation services (commonly referred to as promotion fare) whose purpose is to eliminate their competitors. As such, the winner will be monopolizing the market and harming the ecosystem in it. The aims of this paper is to examine whether the Indonesian competition law can address the unfair business competition within e-hailing industry. It is found that e-hailing industry in Indonesia has been exposed to the practice of cash-burning by the business players. Competition law is needed to foster fair competition among the business players in e-hailing industry. Furthermore, the Government needs to formulate the good competition policy and ensure its enforcement.